Milimeter-wave Profiled Corrugated Horns for the QUaD Cosmic Background Polarization Experiment - Murphy, J.Anthony; Gleeson, E.; Cahill, G.; Lanigan, W.; O'Sullivan, Créidhe; Cartwright, E.; Church, S.E.; Hinderks, J.; Kirby, E.; Thompson, K.; Rusholme, B.; Gear, W.K.; et al. (Springer Verlag, 2005)
In this paper we report on the design and validation process for the profiled corrugated horn antennas, which feed the bolometer array of a cosmology experiment known as QUaD located at the South Pole. This is a cosmic radiation polarization project, which demands precise knowledge and control of the optical coupling to the signal in order to map the feeble E- and B0polarization mode structure. The system will operate in two millimeter wavelength bands at 100 and 150 GHz. The imaging horn array collects the incoming signal via on-axis front-end optics and a Cassegrain telescope, with a cold stop in front of the array to terminate side-lobe structure at an edge taper of -20dB. The corrugated horn design process was undertaken using in-house analytical software tools, based on modal scattering, specially developed for millimeter-wave profiled horn antennas. An important part of the instrument development was the validation of the horn design, in particular to verify low edge taper levels and the required well-defined band edges. Suitable feed horn designs were measured and were found to be in excellent agreement with theoretical predictions.